Scaling-up adoption of improved technologies: The impact of the promotion of row planting on farmers' teff yields in Ethiopia - Joachim Vandercasteelen; Mekdim Dereje; Bart Minten; Alemayehu Seyoum Taffesse (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
Adoption of yield - increasing technologies is seen as a key driver to increase agricultural production in Sub-Saharan Africa. There is, however, a lack of empirical evidence on the impact of programs aiming to scale-up the adoption of improved technologies from research settings to the farm level. To fill this gap, this paper assesses the impact of the promotion of a new agricultural technology, i.e. row planting at reduced seed rate, on farmers' teff yields in Ethiopia. The results of a randomized control trial show that the program to scale-up row planting on average has a positive effect on teff yield. Depending on the measure of yield used, we find increases between 2 percent - but not statistically significant - and 22 percent. These findings are in contrast with larger yield increases found on village demonstration plots and in more controlled settings, as well as with the yield increase expected by teff farmers. The differences seemingly are linked to problems in implementation of the program and of its recommendations, methodological issues, and likely over-optimism on the potential of row planting in real farm settings.
Keywords: 330; Ethiopia; teff yield; row planting; adoption of new technology